2012
DOI: 10.1002/ppsc.201200047
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Visible Emission of Luminescent Hybrid Nanoparticles Incorporating Two Complementary Luminophores: ZnO Nanocrystals and [Mo6Br14]2− Nanosized Cluster Units

Abstract: ZnO nanocrystals and Mo6 clusters are embedded in silica nanoparticles using a modified Stöber process. The resulting materials offer tunable emission properties with a broad emission covering almost the entire visible range for an excitation wavelength of 365 nm. The luminescence properties of the nanoparticles remain stable even when the particles are dispersed in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Since the energies of these bands are similar for Mo 6 Cl 14 2− and Mo 6 Br 14 2− , it is believed that both highest occupied and lowest unoccupied molecular orbitals are largely metal centered [61]. Other researchers have revealed that Mo 6 NCs can be integrated with other material systems, such as semiconducting quantum dots [46], silica [47] and copolymer [48]. In an earlier effort, Grasset et al [46] presented the preparation and characterization of a novel organosol and solid state nanocomposite, namely (( n -C 4 H 9 ) 4 N) 2 Mo 6 Br 14 @ZnO, by using an original and simple bottom-up process.…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the energies of these bands are similar for Mo 6 Cl 14 2− and Mo 6 Br 14 2− , it is believed that both highest occupied and lowest unoccupied molecular orbitals are largely metal centered [61]. Other researchers have revealed that Mo 6 NCs can be integrated with other material systems, such as semiconducting quantum dots [46], silica [47] and copolymer [48]. In an earlier effort, Grasset et al [46] presented the preparation and characterization of a novel organosol and solid state nanocomposite, namely (( n -C 4 H 9 ) 4 N) 2 Mo 6 Br 14 @ZnO, by using an original and simple bottom-up process.…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
“…These emissive properties have been used successfully to sensitize Er 3+ complex emission in the infrared region and within the polymer matrix. Aubert et al [47] successfully stabilized the ZnO nanocrystals in the presence of water using polyvinylpyrrolidone for their further coencapsulation along with [Mo 6 Br 14 ] 2 cluster units in silica to form ZnO–Cs 2 [Mo 6 Br 14 ]@SiO 2 nanoparticles using a modified Stöber process. These nanoparticles exhibit tunable emission properties with a broad emission spectrum covering almost the entire visible range for an excitation wavelength of 365 nm (figure 7).…”
Section: Synthesis Approaches For Pt Mo Bi and Alloy Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, ZnO-Cs 2 Mo 6 Br 14 colloidal solutions were stabilized by addition of polyvinylpyrrolidone (PVP) in the presence of water and could be therefore used for the preparation of transparent and luminescent polymer thin films. [19] These films were transparent in the visible range, and produced a large emission band covering almost the entire visible range under excitation at 325 nm. Nevertheless, because of the low emission efficiency of the bromide cluster, the fine tuning of their luminescence properties was not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its hexagonal-wurtzite crystal structure, Zn and O terminated polar surfaces, different growth rates of the diverse crystal planes, quasi-1-Dimensional (Q1D) nanostructures and complex morphologies from ZnO can be synthesized. The direct bandgap which lies in the near ultraviolet -(UV) spectral region and alternating Zn and O stacking layers enable ZnO nanostructures to exhibit exceptional optical, luminescent 6,7) and electrical properties 5,[8][9][10][11] . Bendability is also a very important property required for different applications but bulk ceramics or metal oxides are brittle in nature [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%